A STUDY OF METAPHOR IN NEWSPAPERS (ENGLISH VERSUS VIETNAMESE) - Hồ Vi Nữ Mỹ Linh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study mainly investigated into the syntactic and semantic features of metaphorical expressions in English and Vietnamese newspapers. This thesis also found out the similarities, differences and the frequencies of occurrence of metaphor in newspaper language in both languages. The study is collected more than 400 samples from English and Vietnamese articles then analyzed on syntactic and semantic aspects based on the basis of the traditional view and contemporary view. With the findings in newspapers, semantic and syntactic features of metaphor are partly proposed to contribute to better teaching and learning English as a foreign language, specifically to better the awareness of learners in translating and writing an article effectively.